Occurrence and the state of a tudor repeat protein in the development of Xenopus laevis - Mostafa, Md Golam (Jahangirnagar University Journal of Biological Sciences, 2016)
The Xenopus tudor repeat (Xtr) protein of the unfertilized and fertilized eggs at different intervals, and embryos of different stages was compared by immunoprecipitating with anti-Xtr monoclonal antibody, followed by Western blotting using anti-Xtr antibody. Besides the Xtr of 270 kDa, another band of Xtr below 150 kDa, was detected reproducibly after fertilization of the eggs. This result suggested that a part of Xtr was degraded after fertilization. The screening profile of the existence of Xtr and the distribution of degradation from unfertilized eggs to the nerula stage embryos showed that in the unfertilized eggs there was no occurrence of degradation. But it was visualized just after 20-minutes of fertilization and lasted up to the gastrula stage. Interestingly, the degradation could not be detected beyond this stage of development. Probably, the Xtr protein was degraded following the activation of the eggs because previous investigations suggested that Xtr acted after fertilization or activation of the eggs. Jahangirnagar University J. Biol. Sci. 3(2): 1-8, 2014 (December)